The regulation doses of sulfur dioxide with the aid of preparations, based on glutathione of yeasts in the production of pink table wine - Bilko, Marina; Tenetka, Alina (My University, 2013)
This research presents study the influence of partial sulfur dioxide replacement by preparations based on yeast glutathione and tannin on the quality of rose table wine. Це дослідження представляє вивчення впливу заміни діоксиду сірки часткового препаратами на основі дріжджів глутатіону і таніну на якість троянди столового вина.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; rose wine; glutathione; induced oxidation; рожеве вино; глутатіон; індуковане окислення; розовое вино; глутатион; индуцированное окисление